1-Palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) attenuates gemcitabine-induced neutrophil extravasation - Jinseon Jeong; Yong-Jae Kim; Do Young Lee; Byoung-Gon Moon; Ki-Young Sohn; Sun Young Yoon; Jae Wha Kim (Cell & Bioscience, 2019)
Abstract Cancer patients treated with chemotherapy often experience a rapid decline of blood neutrophils, a dose-limiting side effect called chemotherapy-induced neutropenia. This complication brings about dose reductions or cessation of chemotherapy during treatment of cancer patients because a rapid decline of neutrophil counts increases susceptibility to infection. Here, we found that 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) attenuates gemcitabine-induced neutrophil extravasation via the inhibition of neutrophil-attracting chemokine production in macrophages using in vivo and in vitro approaches. A single intraperitoneal administration of gemcitabine induced the migration of circulating neutrophils into the peritoneal cavity in normal mice, and PLAG effectively decreased neutrophil migration by inhibiting the expression of adhesion molecules, L-selectin and LFA-1. Inhibition of CXCR2 by its antagonist, reparixin, abrogated gemcitabine-induced neutrophil migration, indicating that chemokines produced by gemcitabine mainly support neutrophil activation. In vitro experiments demonstrated that PLAG inhibited NADPH oxidase 2 (NOX2)-mediated reactive oxygen species production induced by gemcitabine, which is the upstream of MIP-2 and/or CXCL8. Importantly, PLAG down-regulated gemcitabine-induced membrane translocation of the cytosolic NOX subunit, Rac1, and phosphorylation of p47phox. The activation of upstream signaling molecules of p47phox phosphorylation, phospholipase C β3 and protein kinase C, were effectively regulated by PLAG. We also demonstrated that 1-palmitoyl-2-linoleic-3-hydroxyl-rac-glycerol (PLH), the natural form of diacylglycerol, has no effects on gemcitabine-induced CXCL8 production and dHL-60 migration, suggesting that an acetyl group at the third position of the glycerol backbone may have a key role in the regulation of neutrophil activation. Altogether, this study suggests the potential of PLAG as a therapeutic strategy to modulate chemotherapy-induced neutrophil activation for cancer patients undergoing chemotherapeutic treatment.